Моделювання динаміки рівня оплати праці науковців та її впливу на розвиток науково-технічного потенціалу України - Бєлов, О. В.; Бутенко, Таміла; Belov, A.; Butenko, Tamila (Запоріжжя : 2023, 2023)
UA: Досліджено динаміку чисельності науковців, які виконували НДР в цілому по Україні і окремо по регіонах з 1995 року, визначено темпи росту, регіональну структуру, її динаміку і побудовано моделі для прогнозування виявлених тенденцій. Здійснено аналіз динаміки матеріального стимулювання науковців, які виконували НДР. Побудовано моделі для його прогнозування. Показано, що неухильне зменшення величини даного показника, яке спостерігається у переважній більшості регіонів України є індикатором посилення негативної динаміки їх науково-технічних потенціалів, і згортання науково-технічного і, відповідно, інноваційного розвитку в країні. EN: Science is the main production force of the knowledge economy, which is formed in the postindustrial society of the developed countries of the EU. The level of competitiveness of the country depends on its state and development. Over the past decade, the EU has been increasing its funding for R & D, increasing the number of academics and improving the prestige of a scientist's profession. In Ukraine, during all years of independence, there are reverse trends in the development of science, which can become a significant obstacle not only for the country's accession to the EU, which it has been pursuing in recent times, but also for ensuring its socio-economic development in the medium and long run. The object of the article's research is the scientific and technical capacity of Ukrainian regions. The subject of the research is the dynamics of the number of scientific and technical personnel of Ukrainian regions of Ukraine. The purpose of the article is To model the researchers' remuneration dynamic's level and to determine its influence on the dynamics of the personnel component of the R&D capacity advancement in Ukraine. The dynamics of the number of scientists who carried out research and development in general in Ukraine and separately in its regions from 1995 has been studied, the growth rates, regional structure and dynamics have been identified, models for forecasting the revealed tendencies has been created. The analysis of the dynamics of labor remuneration of scientists, who did R & D, has been done. The " researchers' remuneration dynamic's level" is calculated, which is equal to the ratio of the average monthly salary of scholars to the average monthly wage for a certain region. Models for its forecasting have been created. It is shown that the steady reduction of this indicator, which is observed in the vast majority of regions of Ukraine, leads to an increase in the negative dynamics of their scientific and technical capacity and it is an indicator of the curtailment of scientific and technological and, accordingly, innovation development in the country.
Modeling the researchers' remuneration dynamic and its influence on the r&d capacity advancement in Ukraine
Keywords: науково-технічний потенціал; стратегічний розвиток; інновації; НДР; науково-технічний персонал; scientific and technical capacity; strategic development; innovations; R&D; scientific and technical personnel